Integrating Criminology and Law Enforcement: Explaining Child Sexual Violence in Indonesia - Vira Auliya Juliharto; Lisnawaty W. Badu; Avelia Rahmah Y. Mantali; Francis Daniel Mbilinyi (al-Battar: Jurnal Pamungkas Hukum, 2026)
Child sexual violence remains a significant challenge in Indonesia despite the existence of comprehensive legal protections. Previous studies have predominantly emphasized normative legal analysis or crime statistics, while limited attention has been given to integrating criminological perspectives with local law enforcement practices. This study aims to identify the criminogenic factors contributing to child sexual violence in Gorontalo City and evaluate the effectiveness of law enforcement responses in addressing such crimes. An empirical legal research design with a qualitative approach was employed. Primary data were collected through in-depth interviews with investigators from the Women and Children Protection Unit (PPA) of the Gorontalo City Police, supported by field observations and document analysis. The data were analyzed using qualitative descriptive techniques to identify recurring patterns and institutional challenges. The findings reveal that child sexual violence is driven by multiple interrelated factors, including inadequate parental supervision, permissive social environments, offenders' psychological characteristics, and weak social control mechanisms. Most cases occur within close interpersonal relationships, particularly involving family members or intimate partners, where manipulation, persuasion, and abuse of trust constitute the dominant modus operandi. Law enforcement responses combine repressive measures through criminal investigation and prosecution with preventive initiatives, including public awareness campaigns and inter-agency collaboration. However, these efforts remain constrained by evidentiary limitations, victims' psychological trauma, and low levels of public legal awareness. This study demonstrates that integrating criminological analysis with local law enforcement practices provides a more comprehensive understanding of child sexual violence and highlights the need to strengthen family-based prevention, institutional capacity, and community-based child protection mechanisms to improve criminal justice policies and victim protection.